2022
DOI: 10.1007/s42773-022-00178-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term biochar addition significantly decreases rice rhizosphere available phosphorus and its release risk to the environment

Abstract: Phosphorus (P) availability, diffusion, and resupply processes can be altered by biochar addition in flooded rice rhizosphere, which controls the risk of P release to the environment. However, there are few in-situ investigations of these rhizospheric processes and effects. To explore the effects of biochar addition on soil P availability, high-resolution dialysis (HR-Peeper), diffusive gradients in thin films (DGT), and zymography techniques were used to provide direct evidence in the rice rhizosphere at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Notably, prior studies have tended to focus more on soil processes and less on rhizosphere processes. In our investigation using the DGT technique, we discovered a significant reduction in rice rhizosphere available P after 9 years of biochar addition in the field (Chen et al 2022). However, the lack of available data on long-term effects of biochar on nutrient cycling, particularly in the rhizosphere zone, has been limiting our ability to include biochar amendment as one of the best management practices on a broad scale across the globe (Wei et al 2019).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Notably, prior studies have tended to focus more on soil processes and less on rhizosphere processes. In our investigation using the DGT technique, we discovered a significant reduction in rice rhizosphere available P after 9 years of biochar addition in the field (Chen et al 2022). However, the lack of available data on long-term effects of biochar on nutrient cycling, particularly in the rhizosphere zone, has been limiting our ability to include biochar amendment as one of the best management practices on a broad scale across the globe (Wei et al 2019).…”
Section: Introductionmentioning
confidence: 89%
“…The urea and potassium chloride (KCl) application dozes were 250 kg N ha −1 (in a ratio of 3:4:3 at basal, tillering, and jointing stages) and 60 kg K 2 O ha −1 , respectively. Detailed information on biochar, soil and fertilization methods used in the field experiment can be found in Chen et al (2022). The biochar used in the field was derived from rice straw and produced through pyrolysis at a temperature of 500 °C for 8 h, with a heating rate of 5 °C min −1 .…”
Section: Soil and Biocharmentioning
confidence: 99%
“…In all cases, the DGT was reported as a useful tool in assessing the impact of amendments on P availability. Chen et al (2022) studied the fluxes of P in the rice rhizosphere using DGT, high-resolution dialysis (HR-Peeper), and zymography techniques. DGT measurements indicated that long-term biochar addition to the soil significantly diminished the diffusion and resupply capacity of P from the soil solid phase to the soil solution, thus lessening the risk of P release into the environment (Chen et al 2022).…”
Section: Dgt Applications To Nutrient Labile Fractions In Soilmentioning
confidence: 99%
“…DGT has the potential to be deployed in situ, although this direction has not yet been extensively used until now due to potential issues related to the deficiency of parameter control, mainly regarding the soil moisture. Several reports on particular cases of DGT application to wet soils, such as rice fields, were published (Wang et al 2021 ; Chen et al 2022 ; Wang et al 2022a ).…”
Section: Dgt Applicability For Element Availability In Soil Dgt Proce...mentioning
confidence: 99%
See 1 more Smart Citation